THE LINGUOPOETIC STRUCTURE OF HUMOR IN “SHUM BOLA” BY GAFUR GULAM - Berdiyeva, Sitora (International Conference on Business & Management, 2026)
“Shum bola” by Gafur Gulam is considered one of the most significant examples of Uzbek children’s literature, in which humor functions not only as an aesthetic device but also as a fundamental constructive element of artistic thinking. In the work, comic effect is generated through different levels of language and operates as an integrated linguopoetic system. In particular, the interaction of lexical-semantic, syntactic, and discursive devices creates a complex artistic model of humor. Therefore, studying humor in “Shum bola” as a linguopoetic phenomenon makes it possible to reveal the pragmatic, stylistic, and cultural layers of the text.